The role of peripheral centres in Europe - Hans Spilker (Intereconomics, 1975)
The European Regional Conference and the Council of the European Communities are both pursuing a regional policy concept which, on the one hand, focuses on the promotion of economic activity in areas of scanty development and, on the other, aims at curbing rather than promoting the development of central urban areas. In the following paper — read to the First Conference of Local Authorities in European Border Regions at Galway, Ireland, on October 15 to 17 — Dr Spilker is dealing with the question whether this concept lends itself to successful application in the peripheral regions of Europe.
Keywords: 330; Regional Policy